PROJETO FORMATIVO PREVISTO NA BASE NACIONAL COMUM PARA A FORMAÇÃO INICIAL DE PROFESSORES DA EDUCAÇÃO BÁSICA: IMPLICAÇÕES PARA O CURSO DE PEDAGOGIA - FONSECA, MARYLIA GABRIELA ORTIS DA (2024)
Recent curricular reforms in the Basic Education field, especially after implementation of the National Common Curricular Base (BNCC/2017), led to significant changes in the teacher training area, generating curricular reforms in teaching degrees, driven by the justification that teachers would not be prepared to meet the demands of the 21st century. Thereunto, the Common National Base for the Initial Training of Basic Education Teachers (also called BNC-Formação in Portuguese) is presented as a solution to the problems surrounding teacher training, delimiting the practice, also standardizing the training process for the unique and exclusive fulfillment of skills and competencies foreseen by the BNCC/2017. In this context, regulations prescribe significant changes to the curricular structure of the courses, and aim at training a new type of worker, focused on the urgent needs of capital. In the search to understand the main effects of BNC Formação, especially regarding to the Pedagogy faculty, this dissertation is structured around the following problem: What is the BNC-Formação training project, and what are the main implications for the Pedagogy faculty? Based on the central question of the study, other concerns that permeate this investigation are dismembered, namely: What is the position of researchers in the field on the new regulations? Are there private agents involved in directing this teacher training policy? What are theoretical and methodological references of this resolution? What type of teachers training is wanted? What could this regulation entail for the Pedagogy faculty if it is implemented? To support and substantiate the analyzes of this study, the method used was historical-dialectical materialism, aiming at developing an understanding of the reality of the object from the totality and its contradictions. Thereunto, the analyzes were based on the writings by Antonio Gramsci, mainly regarding the categories of State, Hegemony and Educational Policies. It is worth noting that this study also has a bibliographic and documentary nature. Therefore, to make appropriate considerations about the object, which is still in the process of dispute, support came from authors and researchers from entities representing education, such as ANFOPE, ANPED, ANPAE, academic production mapping, manifestos and audiovisual resources made available mainly through lives on YouTube, as well as regulations and laws published by the Ministry of Education and the National Education Council. Based on this assumption, it should be noted that the dissertation is presented in three chapters, in addition to the introduction, the first being intended for the survey, categorization and analysis of academic productions, available on the CAPES Journals Portal and in the CAPES Catalog of Theses and Dissertations. Initially, it was analyzed how BNC-Formação was already being portrayed in the academic environment, to build contributions on discussions on the topic, emphasizing the positioning of the scientific-academic community. The second chapter highlights the relationship between the State and conduct of Educational Policies, especially about the reform of the Brazilian State in 1995, which adopted neoliberal trends in the construction and direction of policies in the Brazilian educational sphere. Furthermore, this chapter also identifies the concepts, bases and foundations that permeate the BNC-Formação document, highlighting the main references adopted to build a new teacher training policy. Finally, chapter three highlights an analysis of the Pedagogy course based on Regulations CNE/CP n° 1/2006, CNE/CP n° 2/2015, as well as CNE/CP n° 2/2019, identifying the main concepts and curricular structure defined in each regulation, in addition to the different teacher training projects. This chapter also outlines the main implications for the faculty in accordance with BNC-Formação regulations, based on documents, manifestos and rejection notes published by associations representing education. Wherefore, it is noteworthy that the approval and urgency of implementation of BNC-Formação follows a process coordinated with BNCC/2017, searching for an educational system standardization to meet interests linked to private agents and capital interests, delimited mainly in the 2030 Agenda. The requirement to develop skills and abilities in teacher training eliminates any possibility of solid training, disrupting the real need for the role of the teacher in society, which contributes to the construction of social emancipation, as well as to the transformation of the context in which it operates, aiming at a just, egalitarian, and democratic society for all.